Temporal changes analysis of soil properties associated with Ganoderma boninense Pat. infection in oil palm seedlings in a controlled environment - Abdul Aziz, Mohd Hamim; Bejo, Siti Khairunniza; Wayayok, Aimrun; Hashim, Fazirulhisyam; Kondo, Naoshi; Noor Azmi, Aiman Nabilah (MDPI AG, 2021)
Basal stem rot (BSR) disease of oil palm (Elaeis guineensis Jacq.) spreads through the contact of the plant roots with Ganoderma boninense (G. boninense) Pat. inoculum in the soil. The soil properties can be altered by growing seedlings with or without G. boninense inoculum. In the early stage of infection, the symptoms are difficult to detect. Therefore, an understanding of the environmental soil conditions of the plant is crucial in order to indicate the presence of the fungus. This paper presents an analysis of the temporal changes of the soil properties associated with the G. boninense infection in oil palm seedlings. A total of 40 seedlings aged five months were used in the study, comprising 20 inoculated (infected seedlings: IS) and 20 control (healthy seedlings: HS) seedlings. The seedlings were grown in a greenhouse for six months (24 weeks) under a controlled environmental temperature and humidity. The data of the soil moisture content (MC in %), electrical conductivity (EC in µS/cm), and temperature (T in °C) for each seedling were collected daily using three MEC10 soil sensors every hour and then transferred to the ThingSpeak cloud using a 3G Internet connection. Based on the results, the mean MC and EC showed a decreasing trend, while the mean T showed an increasing trend in both HS and IS during the six-month monitoring period. The overall mean in both the monthly and weekly analysis of MC, EC, and T was higher in HS than IS. However, in the monthly analysis, a Student’s t-test at a 5% significance level showed that only the soil MC and EC were significantly different between HS and IS, while in the weekly analysis, HS was significantly different from IS in all parameters. This study suggests that soil MC, EC, and T can be used as indicators of the G. boninense infection, especially for the weekly data.